Molecular Epidemiology and Colistin-Resistant Mechanism of mcr-Positive and mcr-Negative Escherichia coli Isolated From Animal in Sichuan Province, China - Li, Fulei; Cheng, Ping; Li, Xiaoting; Liu, Ruimeng; Liu, Haibin; Zhang, Xiuying (Frontiers in Microbiology, 2022)
Colistin is the last line of defense for the treatment of multidrug-resistant gram-negative bacterial infections. However, colistin resistance is gradually increasing worldwide, with resistance commonly regulated by two-component system and mcr gene. Thus, this study aimed to investigate molecular epidemiology and colistin-resistant mechanism of mcr-positive and mcr-negative Escherichia coli isolates from animal in Sichuan Province, China. In this study, a total of 101 colistin-resistant E. coli strains were isolated from 300 fecal samples in six farms in Sichuan Province. PCR was used to detect mcr gene (mcr-1 to mcr-9). The prevalence of mcr-1 in colistin-resistant E. coli was 53.47% (54/101), and the prevalence of mcr-3 in colistin-resistant E. coli was 10.89% (11/101). The colistin-resistant E. coli and mcr-1–positive E. coli showed extensive antimicrobial resistance profiles. For follow-up experiments, we used 30 mcr-negative and 30 mcr-1–positive colistin-resistant E. coli isolates and E. coli K-12 MG1655 model strain. Multi-locus sequence typing (MLST) of 30 strains carrying mcr-1 as detected by PCR identified revealed six strains (20%) of ST10 and three strains (10%) of each ST206, ST48, and ST155 and either two (for ST542 and 2539) or just one for all other types. The conjugation experiment and plasmid replicon type analysis suggest that mcr-1 was more likely to be horizontally transferred and primarily localized on IncX4-type and IncI2-type plasmid. The ST diversity of the mcr-1 indicated a scattered and non-clonal spreading in mcr-1–positive E. coli. Twenty-eight mcr-negative colistin-resistant E. coli isolates carried diverse amino acid alterations in PmrA, PmrB, PhoP, PhoQ, and MgrB, whereas no mutation was found in the remaining isolates. The finding showed the high prevalence of colistin resistance in livestock farm environments in Sichuan Province, China. Our study demonstrates that colistin resistance is related to chromosomal point mutations including the two-component systems PhoP/PhoQ, PmrA/PmrB, and their regulators MgrB. These point mutations may confer colistin resistance in mcr-negative E. coli. These findings help in gaining insight of chromosomal-encoded colistin resistance in E. coli.